New Information on the Species Composition of Zooplankton Organisms of Khadicha Lake in Bukhara Region (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The article is the first to establish the presence of 36 species of zooplankton organisms in Lake Khadicha, located in the Bukhara region. The names of the identified species are given in the table and their comparative analysis was carried out.